2002
DOI: 10.1262/jrd.48.399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Density Gradient Osmolality on Specific Gravity of Bull Sperm and Their Separation, but Not on the Basis of Sex.

Abstract: Abstract.The most effective quantitative separation of ejaculates of semen into subsets of sperm differing in quality by density gradients requires information on the specific effects of processing conditions on sperm density. Reported density of bull sperm varies greatly. This research was undertaken to study the effects of gradient osmolality on sperm density and on separation using gradients with low viscosity and low toxicity to sperm. Semen was available from bulls used for artificial insemination. Cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lindahl and Kihlström [ 97 ] reported normal bull sperm density varying between 1.241 and 1.334 g/mL. On the other hand, Lavon et al [ 98 ] reported a range from 1.0376 to 1.0927 g/mL, because the density of sperm may change with age [ 99 ]. The basis of this separation type is a colloidal medium formed by silica particles coated with covalently bonded hydrophilic silane in HEPES [ 100 ].…”
Section: Centrifugation Techniquesmentioning
confidence: 99%
“…Lindahl and Kihlström [ 97 ] reported normal bull sperm density varying between 1.241 and 1.334 g/mL. On the other hand, Lavon et al [ 98 ] reported a range from 1.0376 to 1.0927 g/mL, because the density of sperm may change with age [ 99 ]. The basis of this separation type is a colloidal medium formed by silica particles coated with covalently bonded hydrophilic silane in HEPES [ 100 ].…”
Section: Centrifugation Techniquesmentioning
confidence: 99%